Effects of Nut Consumption on Colon Cell Proliferation and Apoptosis (P06-058-19) - Nakagawa, Ashley (Curr Dev Nutr, 2019)
OBJECTIVES: An imbalance between colon cell proliferation and apoptosis increases one's risk of colon cancer. Some studies have shown an inverse relationship between nut consumption and colon cancer; however, the underlying mechanism is still not elucidated. This study aimed to determine if mixed nut or single nut (pistachio) consumption is able to decrease colon cancer risk by modulating colonic cell proliferation and apoptosis. It was hypothesized that rats consuming nut diets exhibit fewer colonic proliferating cells and greater apoptotic cells compared to a control. METHODS: Thirty 21-day-old Sprague Dawley male rats were assigned to one of three isocaloric diets: control diet containing no nuts, pistachio diet (8.1% w/w), or mixed nut diet (7.5% w/w) for 8 weeks. The mixed nut diet contained cashews, almonds, Brazil nuts, pecans, macadamia nuts, walnuts, pistachios, and peanuts. Proliferating colonic cells were marked using Ki-67 quantitative immunostaining and apoptotic cells with Terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL) assay. Cells clearly stained as proliferative and apoptotic were divided by the total cells in each crypt column, multiplied by 100 to determine proliferation and apoptosis indices. The proliferative zone was determined as 100 times the location of the highest labeled proliferating cell, divided by the total number of cells per crypt. RESULTS: The majority of proliferating cells were located near the bottom of the colonic crypt and apoptotic cells were found in the upper part of the crypt (P < 0.05). No significant differences were found for proliferating index, proliferative zone and apoptotic index among all three experimental diet groups. CONCLUSIONS: Some clinical and experimental studies show the protective effects of nut consumption against colon cancer. Our results indicate that the beneficial effects of nut consumption in colon cancer prevention may be explained by a different mechanism rather than modification of cell proliferation or apoptosis. Additional markers for cell proliferation and apoptosis may need to be used to confirm our results. Other potential mechanisms such as oxidative stress, DNA damage and repair enzymes should be further investigated. FUNDING SOURCES: American Heart Association (16GRNT31360007).